TEACHING NAHW AND SHARF BY USING WHATSAPP (A CASE SUDY AT â€œBISAâ€ FOUNDATION IN DEPOK, WEST JAVA, INDONESIA) / ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù†ØÙˆ Ùˆ Ø§Ù„ØµØ±Ù Ø¹Ø¨Ø± Ø§Ù„ÙˆØ§ØªØ³Ø£Ø¨ (Ø¯Ø±Ø§Ø³Ø© ØØ§Ù„ÙŠØ© ÙÙŠ Ù…Ø¤Ø³Ø³Ø© "Ø¨ÙŠØ³Ø§" Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¯ÙŠØ¨ÙˆÙƒ Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ§) - Ana Rizkiya (Lughawiyah: Journal of Arabic Education and Linguistics, 2021)
This study aims to reveal the process of teaching nahw and sharf via Whatsapp at BISA Foundation, Depok. The researcher used qualitative method in a case study design. To collect the data, the researcher did observation, interviewed the leader, several supervisors and assistants, and distributed online questionnaire to students in nahw and sharf classes using google form. The result described that nahwu and sharf have been tought via Whatsapp since 2013 and was free. Nahw learning is carried for four months and sharf learning is for two months. The textbooks used are al-Nahw lil Mubtadi’in and al-Sharf lil Mubtadi’in. Learning materials are delivered in the forms of written texts, audio, and video. Lessons are held every day except Wednesdays. Teaching and learning is carried out in several activities namely explaining, discussing, and assigning. Students’ learning achievement is measured by giving weekly assignment and final examination. The advantages of teaching nahw and sharf using Whatsapp are that it is cheap and can be carried out everywhere easily. Whereas, the weaknesses are personal problems, the program itself, and technical aspect